Atrial fibrillation during hospitalization for acute st-segment elevation myocardial infarction: prevalence, predictors, therapeutic impact and mortality. (3rd May 2023) - Carias, M; Paralta, M; Almeida, A; Claudio, F; Rocha, R; Picarra, B; Bento, A; Trinca, M
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The presence of Atrial Fibrillation (AF) in Acute Myocardial Infarction (AMI) is an important challenge in antiplatelet and anticoagulant therapy and may have an impact on the prognosis of these patients. Purpose: To determine the incidence of AF during hospitalization for ST-elevated AMI (STEMI), identify possible predictors of its onset and assess its impact on therapy and mortality. Methods: We studied 3254 patients with the diagnosis of STEMI included in a multicenter national registry. We considered 2 groups: patients with AF and patients without AF. Age, gender, cardiovascular and non-cardiovascular history, number of vessels with lesions, number of angioplasties performed, therapy performed at admission and at discharge were recorded. Left ventricular function (LVF), presence of heart failure (HF), the need for invasive mechanical ventilation, mechanical complications, stroke, major hemorrhage, and high-grade atrioventricular block (AVB) were evaluated. In-hospital mortality was compared. Multivariate analysis was performed to identify predictors of AF and to assess the impact of AF on in-hospital mortality. Results: The presence of AF was found in 6.1% (197 patients). The patients with AF were older (71±12 vs 62±14 years; p<0.001), higher prevalence of females (34.5% vs 24.4%, p=0.002), of hypertension (72.4% vs 59.6%, p<0.001), valvular disease (3.7% vs 1.1%, p=0.008), HF (5.6% vs 1.8%, p=0.002), stroke (9.6% vs 5.6%, p=0.021) and chronic renal failure (6.2% vs 2.8%, p=0.007). At the time of coronary angiography, there were no differences in the number and type of vessels with lesions. Patients with AF received more therapy at admission and at discharge with vitamin K antagonists (7.7% vs 1.5% and 12.3% vs 2.5%, p<0.001), diuretics (59.4% vs. 24.3% and 51.3% vs 19.3%, p<0.001), aldosterone antagonists (27.0% vs 12.0% and 25.0% vs 11.1% p<0.001), amiodarone (67.9% vs 4.1% and 37.4% vs 1.6%, p<0.001) and digoxin (10.2% vs 0.3% and 2.6% vs 0.3%, p<0 .05). The presence of AF was associated with worse LVF (p<0.001), higher prevalence of HF (46.2% vs 16.2%, p<0.001), need for invasive mechanical ventilation (10.7% vs 3.4 %, p<0.001), mechanical complications (3.65 vs 1.2%, p=0.013), stroke (4.65 vs 0.8%, p<0.001), AVB (12.7% vs 5.4 %, p<0.001) and major bleeding (6.1% vs 1.8%, p<0.001). In-hospital mortality was higher in patients with AF (13.7% vs 4.6%, p<0.001). By multivariate analysis, the presence of AF per se was not an independent predictor of in-hospital mortality. The following were identified as independent predictors of AF: age and history of HF. Conclusion: In our population of patients with STEMI, the incidence of AF was 6.1% and is associated with an increase in complications and in-hospital mortality. Age and history of HF were independent predictors of AF.